(untitled) (Fiep Bulletin - online, 2011)
I believe that learning is the individual capacity to perform some type of motor task (Schmidt, 1993). As (Schmidt, 1993) learning results from practice or experience. It is observable, through research, humans, or each individual has a way, a way to assimilate knowledge. There are various strategies used during learning and one of them is the knowledge of result (CR). Golf is an elitist sport in Brazil and does not have many adherents. There is a need for materials and specific spaces. The goal is to put the ball in the hole with the fewest strokes. The break is the main motor skill in this sport. It is necessary to proper positioning and broad knowledge of both the material used, such as the environment and techniques of strokes. This paper aims to detect the performance of the golf swing in academic, who did not practice this sport and the influence of CR (knowledge of results) or extrinsic feedback. As the test sample were surveyed 08 (eight) academic course of Physical Education UCDB divided into two groups where one received the CR and the other not. As data collection instrument was used 01 (a) bat made by hand, 01 (a) official golf ball and 01 (a) plastic cup symbolizing the hole. The analysis was performed using descriptive statistics. The results showed that the students who performed better were those who received feedback. We concluded that knowledge of results helps to teach a task and to improve the outcome.